Influence of primary site on metastatic distribution and survival in stage IV colorectal cancer. Issue 5 (16th May 2017) - Suthananthan, Arul E.; Bhandari, Mayank; Platell, Cameron
Abstract : Background: To assess pattern distribution and prognosis of the three anatomical entities of metastatic colorectal cancer, and influence of treatment of metastases on survival. Methods: Patients presenting with stage IV colorectal cancer (synchronous group), or who developed metastatic recurrence (metachronous group) after initial curative treatment between January 2005 and August 2015 were reviewed. Right sided (cecum to transverse colon), left sided (splenic flexure to sigmoid colon) and rectal cancers were identified. Distribution of metastases were noted as hepatic, lung or peritoneal. Results: Of 374 patients, 276 were synchronous, 98 were metachronous. Metachronous group had a better 3‐year survival (54%, 95% CI: 42–64 versus 33%, 95% CI: 27–39, log rank P = 0.0038). There were equal numbers of right ( n = 119), left ( n = 115) and rectal cancers ( n = 140). Rectal cancers had a higher metastatic recurrence, yet demonstrated better 3‐year survival (right colon 45%, 95% CI: 19–67, left colon 49%, 95% CI: 27–68, rectum 59%, 95% CI: 42–72, P = 0.39) due to higher proportions of metachronous patients undergoing treatment for metastases (40 versus 14%). Over half of all organ metastases spread to liver, with equal distribution from all three anatomical groups. Rectal cancers showed highest preponderance for lung metastases. Conclusion: Rectal cancers have a higher chance of recurring, with a higher metastatic rate to the lung, yet demonstrate better survival outcomes in metastatic colorectal cancer, reflecting the benefit of intervention for metastases.